A Survey of Students' ICT Competencies for Developing Industry-Based Curriculum: An Empirical Study of Papuan Higher Education Students - Fransiskus Xaverius Manggau (STAI Hubbulwathan Duri, 2022)
The Internet of Things (IoT) has emerged as a significant topic in the context of the Fourth Industrial Revolution (Industry 4.0). In the IoT paradigm, digital proficiency plays a critical role. Furthermore, digital competency is considered to be one of the most important abilities in the 21st-century learning framework. This study aims to provide an overview of the digital proficiency of higher education students in Papua. Two hundred and twenty students from the engineering faculty were given the questionnaire on digital competence measurement. A moderate level of digital competence (x 3.1) was discovered in this study, which included hardware and software mastery, self-competence, digital security, collaborative learning in the classroom, and digital development mastery. Furthermore, the findings of this study may be applied to the next stage of designing learning curriculum to increase digital competencies to prepare students for having better knowledge and practical skill of IoT.